The Use of Corn Cob and Leaf Waste (Zea mays L.) as Herbal Support for Malaria Prevention: A Social–Humanities Approach Based on Laboratory Evidence - Wiwit Zuriati Uno; Dian Pratiwi Iman; Rifka Anggraini Anggai; Mahdalena Sy Pakaya; Sri Manovita Pateda (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
Corn cobs and corn leaves (Zea mays L.) are abundant agricultural wastes with potential bioactive value. This study aimed to evaluate the extraction efficiency, phytochemical profile, and antioxidant activity of corn cob and corn leaf extracts obtained using solvents of different polarities, and to assess their relevance as supportive herbal resources for health promotion. Samples were extracted using ethanol, acetone, and n-hexane, followed by phytochemical screening and antioxidant evaluation using the DPPH method. The results demonstrated that ethanol extracts produced the highest yields and exhibited very strong antioxidant activity, indicated by low IC₅₀ values. These findings suggest that polar phytochemicals, particularly phenolic and flavonoid compounds, are the main contributors to the antioxidant potential of corn waste materials. Overall, this study provides scientific evidence supporting the valorization of corn agricultural waste as a sustainable source of antioxidant-rich herbal materials with potential relevance for oxidative stress management.